CO2‐Triggered Switchable Hydrophilicity of a Heterogeneous Conjugated Polymer Photocatalyst for Enhanced Catalytic Activity in Water. Issue 11 (14th February 2018) - Byun, Jeehye; Huang, Wei; Wang, Di; Li, Run; Zhang, Kai A. I.
Abstract: Water compatibility for heterogeneous photocatalysts has been pursued for energy and environmental applications. However, there exists a trade‐off between hydrophilicity and recyclability of the photocatalyst. Herein, we report a conjugated polymer photocatalyst with tertiary amine terminals that reversibly binds CO2 in water, thereby generating switchable hydrophilicity. The CO2 ‐assisted hydrophilicity boosted the photocatalytic efficiency in aqueous medium with minimum dosage. When CO2 was desorbed, the photocatalyst could be simply regenerated from reaction media, facilitating the repeated use of photocatalyst. Hydrophilicity/hydrophobicity control of the polymer photocatalyst was successfully showcased through a variety of organic photoredox reactions under visible‐light irradiation in water. Abstract : Wet wet wet : A tertiary amine‐tethered conjugated polymer photocatalyst was designed to exhibit switchable hydrophilicity upon CO2 /N2 exchange. The reversible hydrophilicity of the heterogeneous polymer photocatalyst enhances catalytic efficiency and recyclability for organic photoredox reactions in water.